Korea tiger of Asia : the next Japan - British Broadcasting Corporation (Australia : BBC Active, 1995)
This program examines how cheap government loans encouraged the growth of large conglomerates, and how new policies are helping small and medium companies to develop. Discusses the Korean government's use of onerous antibusiness tactics, such as tax audits on those Koreans who buy imported cars. Officials from conglomerates Daewoo, Samsung, and Hyundai discuss the business practices that contributed to their success. A British computer executive discusses ways in which foreign companies can cope with Korean business regulations and customs
Title from container
DVD format
Keywords: Korea (South) -- Economic policy -- 1960-; Korea (South) -- Economic conditions -- 1960-; Korea (South) -- Foreign economic relations